Russkie belye is a new heavyproductive promising variety of vegetable beans (Vicia faba L.) - E. P. Pronina; V. A. Ushakov; I. P. Kotlyar; A. V. Soldatenko (Овощи России)
Relevance. Among vegetable crops beans are leaders in terms of protein and essential amino acids, rich in vitamins, carbohydrates, organic acids, biologically active compounds and microelements, they are classified as functional nutrition. Beans can also be very relevant for modern ecological farming systems. The achievements of domestic selection in this culture are modest. Only 16 varieties of vegetable beans have been included in the State Register of breeding achievements approved for using in 2019; 3 of them (19%) from the Federal Scientific Vegetable Center.The purpose of the work is to create a new midseason high-yielding variety of vegetable beans.Materials and methods. Studies were carried out from 2008 to 2018 on breeding fields of the FSBSI “Federal Scientific Vegetable Center” (Moscow Region, Odintsovo District). We studied samples of vegetable beans from the world collection of VIR and Federal Scientific Vegetable Center for quantitative and qualitative characteristics.Results. As a result selection work for many years, a new mid-season high-yielding variety of vegetable beans with light seeds and a light seed scar has been created. Hybridization was carried out by step crossing in 2009 followed by multiple individual selection. The surface of the beans is smooth, the color in the technical stage of ripeness is green. Seeds are light, egg shaped, have a light scar. The variety has a complex resistance to major diseases. According to the results of the competitive variety testing of 2016 - 2018, a new variety of Russkie belye vegetable beans was transferred to the State variety testing, and in 2019 it successfully passed an expert assessment.